The Role of the Job Characteristics Model in Psychological Well-Being among Employees at a Private University - Ni Made Putri Ariyanti; Anak Agung Sri Sanjiwani (CV. AFDIFAL MAJU BERKAH, 2026)
This study aimed to examine the role of the Job Characteristic Model on employees’ Psychological Well-Being at a private university in Bali. A quantitative approach with a cross-sectional design was employed in this study. The participants consisted of 48 employees selected using a convenience sampling technique. Data were collected through a survey method using the Motivating Potential Score developed by Hackman and Oldham to measure job characteristics and the Psychological Well-Being Scale developed by Ryff to assess psychological well-being. Data analysis was conducted using simple linear regression. The results indicated that the Job Characteristic Model had a significant effect on employees’ Psychological Well-Being, with a significance value of p < 0.05 and a coefficient of determination of 0.210. These findings suggest that job characteristics accounted for 21% of the variance in employees’ psychological well-being, while the remaining variance was influenced by other factors beyond the scope of this study. Higher levels of job characteristic fulfillment are associated with higher levels of psychological well-being among employees. This study extends the application of the Job Characteristic Model within the higher education context in Indonesia and highlights the importance of job design as a key determinant of employees’ psychological well-being.